A century of coping with environmental and ecological changes via compensatory biomineralization in mussels. (21st November 2020) - Telesca, Luca; Peck, Lloyd S.; Backeljau, Thierry; Heinig, Mario F.; Harper, Elizabeth M.
Abstract: Accurate biological models are critical to predict biotic responses to climate change and human‐caused disturbances. Current understanding of organismal responses to change stems from studies over relatively short timescales. However, most projections lack long‐term observations incorporating the potential for transgenerational phenotypic plasticity and genetic adaption, the keys to resistance. Here, we describe unexpected temporal compensatory responses in biomineralization as a mechanism for resistance to altered environmental conditions and predation impacts in a calcifying foundation species. We evaluated exceptional archival specimens of the blue mussel Mytilus edulis collected regularly between 1904 and 2016 along 15 km of Belgian coastline, along with records of key environmental descriptors and predators. Contrary to global‐scale predictions, shell production increased over the last century, highlighting a protective capacity of mussels for qualitative and quantitative trade‐offs in biomineralization as compensatory responses to altered environments. We also demonstrated the role of changes in predator communities in stimulating unanticipated biological trends that run contrary to experimental predictive models under future climate scenarios. Analysis of archival records has a key role for anticipating emergent impacts of climate change. Abstract : Current understanding of organismal responses to change stems from relatively short‐term studies. Most projections lack long‐term observations incorporating the potential for transgenerational phenotypic plasticity and genetic adaption. We describe unexpected temporal responses in biomineralization as a mechanism for resistance to altered environments in the blue mussel Mytilus edulis . We evaluated archival mussel specimens collected regularly between 1904 and 2016, along with records of environmental descriptors and predators. Contrary to global‐scale predictions, shell production increased over the last century, highlighting a protective capacity of mussels for qualitative and quantitative trade‐offs in biomineralization as compensatory responses to altered environments and predator communities.